Methyl 4-chloro-3-nitrobenzoate - Liu, Bo-Nian (International Union of Crystallography, 2008)
In the title compound, C(8)H(6)ClNO(4), the molecules are linked by C—H⋯O interactions to form a chain parallel to the a axis. The chains are further connected by slipped π–π stacking between symmetry-related benzene rings, with a centroid-to-centroid distance of 3.646 (2) Å and an interplanar distance of 3.474 Å, resulting in an offset of 1.106 Å.